Electrochemical Sensors for Detection of Acetylsalicylic Acid - Rene Kizek; Ales Horna; Miroslava Beklova; Petr Babula; David Potesil; Vojtech Adam; Jitka Petrlova; Sona Krizkova; Ladislav Havel; Jiri Petrek; Veronika Supalkova (Sensors, 2006)
Acetylsalicylic acid (AcSA), or aspirin, was introduced in the late 1890s and hasbeen used to treat a variety of inflammatory conditions. The aim of this work was to suggestelectrochemical sensor for acetylsalicylic detection. Primarily, we utilized square wavevoltammetry (SWV) using both carbon paste electrode (CPE) and of graphite pencilelectrode (GPE) as working ones to indirect determination of AcSA. The principle ofindirect determination of AcSA bases in its hydrolysis on salicylic acid (SA), which isconsequently detected. Thus, we optimized both determination of SA and conditions forAcSA hydrolysis and found out that the most suitable frequency, amplitude, step potentialand the composition and pH of the supporting electrolyte for the determination of SA was260 Hz, 50 mV, 10 mV and Britton-Robinson buffer (pH 1.81), respectively. The detectionlimit (S/N = 3) of the SA was 1.3 ng/ml. After that, we aimed on indirect determination ofAcSA by SWV CPE. We tested the influence of pH of Britton-Robinson buffer andtemperature on yield of hydrolysis, and found out that 100% hydrolysis of AcSA wasreached after 80 minutes at pH 1.81 and 90°C. The method for indirect determination ofAcSA has been utilized to analyse pharmaceutical drug. The determined amount of AcSA in the pharmaceutical drug was in good agreement with the declared amounts. Moreover, weused GPE for determination of AcSA in a pharmaceutical drug. Base of the results obtainedfrom stationary electrochemical instrument we used flow injection analysis withelectrochemical detection to determine of salicylates (SA, AcSA, thiosalicylic acid, 3,5-dinitrosalicylic acid and 5-sulfosalicylic acid – SuSA). We found out that we are able todetermine all of detected salicylates directly without any pre-treatment, hydrolysis and so onat units of femtomoles per injection (5 μl).